Consistent estimation of the fixed effects ordered logit model - Gregori Baetschmann; Kevin E. Staub; Rainer Winkelmann (University of Zurich, Department of Economics, 2011)
The paper re-examines existing estimators for the panel data fixed effects ordered logit model, proposes a new one, and studies the sampling properties of these estimators in a series of Monte Carlo simulations. There are two main findings. First, we show that some of the estimators used in the literature are inconsistent, and provide reasons for the inconsistency. Second, the new estimator is never outperformed by the others, seems to be substantially more immune to small sample bias than other consistent estimators, and is easy to implement. The empirical relevance is illustrated in an application to the effect of unemployment on life satisfaction.
Keywords: C23; C25; J28; J64; 330; ordered response; panel data; correlated heterogeneity; incidental parameters; Panel; Logit-Modell; Monte-Carlo-Methode; Schätzung; Zufriedenheit; Arbeitslosigkeit; Schweiz